White Light and Multicolor Emission Tuning in Triply Doped Yb3+/Tm3+/Er3+ Novel Fluoro-phosphate Transparent Glass-ceramics - Ledemi, Yannick [UNESP]; Trudel, AndrÉe-anne; Rivera, Victor; Chenu, SÉbastien; VÉron, Emmanuel; Nunes, Luiz Antonio Oliveira; Allix, Mathieu; Messaddeq, Younes [UNESP] (Royal Society of Chemistry (RSC), 2014)
New Yb3+, Er3+ and Tm3+ doped fluoro-phosphate glasses belonging to the system NaPO3–YF3–BaF2–CaF2 and containing up to 10 wt% of rare-earth ion fluorides were prepared and characterized by differential scanning calorimetry, absorption spectroscopy and up-conversion emission spectroscopy under excitation with a 975 nm laser diode. Transparent and homogeneous glass-ceramics have been reproducibly obtained with a view to manage the red, green and blue emission bands and generate white light. X-ray diffraction as well as electron microscopy techniques have confirmed the formation of fluorite-type cubic nanocrystals at the beginning of the crystallization process while complex nanocrystalline phases are formed after a longer heat-treatment. The prepared glass-ceramics exhibit high optical transparency even after 170 h of thermal treatment. An improvement of up-conversion emission intensity – from 10 to 160 times larger – was measured in the glass-ceramics when compared to the parent glass, suggesting an important incorporation of the rare-earth ions into the crystalline phase(s). The involved mechanisms and lifetime were described in detail as a function of heat-treatment time. Finally, a large range of designable color rendering (from orange to turquoise through white) can be observed in these materials by controlling the laser excitation power and the crystallization rate.